A FUNÇÃO MORFOSSINTÁTICO-SEMÂNTICA DOS ADJETIVOS NAS “NOTAS DE FALECIMENTO” NO JORNAL PRÁCIA - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2013)
This paper analyzes the position of adjectives found in obituaries of priests and nuns at Prácia Newspaper. The relevance of this research consists, besides emphasizing the use and employment of adjectives in the Death Notes, includes analysis of texts having representation and historical nature and the representatives of these writings for the Ukrainian immigrant descendants‟ community of Prudentópolis city and its region, in Paraná State. This research has theoretical contribution of Bechara (2009), Castillo (2010) and Neves (2011), among others, arguing over ante and postposition of adjective in the construction of noun phrases. The analysis on the relationship between the noun and the adjective position in being before or after to it was observed both in the Obituary announcing death news of priests and nuns. Over the nuns Death Notes is possible to identify the emphasis to postposition when described the biography of the deceased, which according to Castilho (2010), is represented as an order less marked in Portuguese. Ante position cases found in nuns Death Notes, mostly describes the works done to the church and the community. Regarding priests Death Notes adjectives appear before or after to the noun not considering his religious role or his actions as an ordinary person. Thus, it was possible to analyze the use of adjectives and how some DN are organized when describing familiar and religious facts associated and others that just mention religious aspects, i.e., the activity practiced (represented) by the deceased for the community.
Keywords: jornal Prácia; notas de falecimento; adjetivos; Prácia newspaper; death notes; adjectives; CNPQ::LINGUISTICA, LETRAS E ARTES::LINGUISTICA